2021
DOI: 10.1136/bmjoq-2021-001522
|View full text |Cite
|
Sign up to set email alerts
|

Nudging healthcare professionals to improve treatment of COVID-19: a narrative review

Abstract: Narrative review © Author(s) (or their employer(s)) 2021. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ. METHODSWe conducted a narrative review to explore the role of nudging in supporting HCPs in the prevention and treatment of COVID-19.Studies eligible for inclusion were: (1) interventions conducted in a clinical setting targeting healthcare personnel, (2) behavioural interventions using the term nudging, (3) randomised controlled trials, quasi-experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…For example, nudging via prescheduled appointments or switching the default option increased COVID-19 vaccination rates ( Bonander et al, 2022 ; Tentori et al, 2022 ). A narrative review indicated that nudging strategies, including default rules, could be important tools for improving the treatment of COVID-19 ( Vilhelmsson et al, 2021 ). However, previous attempts focused on improving health decision-making relevant to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nudging via prescheduled appointments or switching the default option increased COVID-19 vaccination rates ( Bonander et al, 2022 ; Tentori et al, 2022 ). A narrative review indicated that nudging strategies, including default rules, could be important tools for improving the treatment of COVID-19 ( Vilhelmsson et al, 2021 ). However, previous attempts focused on improving health decision-making relevant to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinicians appear to have a higher response to nudges which 'change default options' , or 'enable choice' as opposed to nudges which solely provide information through prompt reminders [21]. Passive and asynchronous nudge interventions, or those non-aligned with patient preferences have been found to be less successful than those that use an active, synchronous intervention that requires immediate action [22,23].…”
Section: Discussionmentioning
confidence: 99%
“… 21 A December 2021 narrative review found that nudging strategies targeting COVID-19 vaccination orders for patients, such as text message reminders, had a positive result. 22 A 2021 systematic review found that clinical nudging interventions that make information more salient are the most successful in improving vaccine uptake. 23 This concept also been tested successfully through randomised control trials.…”
Section: Discussionmentioning
confidence: 99%
“…Nudging has been used in multiple clinical settings to better align health care provider decision-making with established guidelines 21. A December 2021 narrative review found that nudging strategies targeting COVID-19 vaccination orders for patients, such as text message reminders, had a positive result 22. A 2021 systematic review found that clinical nudging interventions that make information more salient are the most successful in improving vaccine uptake 23.…”
Section: Discussionmentioning
confidence: 99%